Cue Utilization and Broad Indicators of Workplace Expertise. (March 2014) - Loveday, Thomas; Wiggins, Mark W.; Searle, Ben J.
Where occupational performance outcomes are difficult to measure, there is a tendency to associate expertise with years of experience and/or previous occupational position. Although useful, these indicators represent composite constructs that embody a number of different variables, only some of which may be strongly associated with the transition to expertise. In identifying an alternative measure of expertise, it is necessary to consider the cognitive processes associated with expert performance, in particular, the role of cue utilization. The present study, conducted in the context of software engineering, was designed to test the relationship between cue utilization and self, peer, and error management indicators of expertise. The results indicated that participants who exhibited relatively higher levels of cue utilization were significantly more likely to self-report engaging in behaviors associated with expert decision making, to be nominated as an expert by their peers, and to demonstrate superior error management when developing solutions to development problems.